Analysis Of The Effectiveness Of The Use Of Local Government Information Systems (SIPD) In The Budget Preparation Process (APBD) At The National Unity And Political Agency Of South Sumatra Province - Didik Prayogi; Nurul Huda (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2026)
The implementation of the Regional Government Information System (SIPD) represents a fundamental paradigm shift in the digital transformation of Indonesian local governance, specifically designed to enhance effectiveness, efficiency, and transparency in the management of the Regional Revenue and Expenditure Budget (APBD). This study aims to conduct a comprehensive analysis of the effectiveness of SIPD implementation in the APBD preparation process at the National Unity and Politics Agency (Badan Kesbangpol) of South Sumatra Province. Utilizing the DeLone and McLean Information Systems Success Model as the theoretical framework, this research evaluates six core dimensions: System Quality, Information Quality, System Use, User Satisfaction, Individual Impact, and Organizational Impact. A quantitative approach was employed using a survey method with 40 respondents comprising budget drafting staff, budget analysts, treasurers, and IT support teams. The data were analyzed using descriptive statistics to determine the level of effectiveness and identify inhibiting factors. The results indicate that the overall effectiveness of SIPD is categorized as "Effective Enough" with an average score of 3.22 on a Likert scale of 1-5. The System Use dimension achieved the highest score (3.48), reflecting a high level of user adoption due to mandatory regulations, while the System Quality dimension received the lowest score (2.93), highlighting significant challenges in IT infrastructure, system response time, and feature customization. The study concludes that while SIPD has been successfully integrated into the agency's workflow and positively impacts organizational accountability, urgent improvements are required in technical infrastructure, user training, and feature customization to optimize its potential.